Pet ownership and its influence on mental health in older adults - Hui Gan, Genieve Zhe; Hill, Anne-Marie; Yeung, P.; Keesing, Sharon; Netto, Julie Anne (2019)
Objectives: With aging, older adults are at risk of a decline in mental health as they experience significant life stressors that are specific to later life. It is thus important to explore the potential of suitable approaches that promote healthy aging, to address the mental health needs of older adults. Pet ownership has been found to be associated with positive mental health outcomes; however, there is limited research on the lived experience and meaning derived from pet ownership. The purpose of this study was to explore pet ownership in community-dwelling older adults and its influence on mental health. Methods: Semi-structured interviews were conducted with 14 community-dwelling older adults who were aged 65 and above and pet owners. Participants were interviewed individually on a single occasion about the meaning derived from the role of pet ownership and howthey perceived that their pet influenced their mental health. Results: Results were analysed using Colaizzi’s phenomenological framework and four themes emerged from the interviews: pets provide (i) comfort and safety; (ii) social inclusion and participation; (iii) purposeful routine and structure; and (iv) a meaningful role. Conclusion: These findings suggest that the role of pet ownership may benefit community-dwelling older adults by providing companionship, giving a sense of purpose and meaning, reducing loneliness and increasing socialisation. These benefits may also increase resilience in older adults against mental health disorders, which may positively influence their mental health outcomes.